2021
DOI: 10.1002/ijc.33460
|View full text |Cite
|
Sign up to set email alerts
|

The mutational landscape and prognostic indicators of pseudomyxoma peritonei originating from the ovary

Abstract: Pseudomyxoma peritonei (PMP) is a rare disorder with unique pathological and genetic changes. Although several studies have reported the clinical features and mutational changes of PMP that originates from the appendix, few studies on PMP originating from the ovary have been reported due to its extreme rarity. In order to characterize the somatic mutational landscape and to investigate the prognosis predicting factors of ovary‐originating PMP, we examined 830 cases of PMP and identified 16 patients with PMP th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…C.PABLO et al revealed that tumor markers CEA and CA199 have high value in clinical application in diagnosis of mucous adenocarcinoma of appendix, and the increasing CA125 while normal HE4 help discriminate between benign and malignant ovarian tumors [1,2]. The patient reported here had elevation of CA199 and CA125, which is of certain value in diagnosis of appendiceal lesions [3]. Michelle Moh et al combined immunohistochemistry to report common SATB (-), SATB2 (+) and CDX-2 (+) in ovarian mucinous tumors, highly indicative of the tumor being derived from the colon or the appendix [2].…”
Section: Discussionmentioning
confidence: 53%
“…C.PABLO et al revealed that tumor markers CEA and CA199 have high value in clinical application in diagnosis of mucous adenocarcinoma of appendix, and the increasing CA125 while normal HE4 help discriminate between benign and malignant ovarian tumors [1,2]. The patient reported here had elevation of CA199 and CA125, which is of certain value in diagnosis of appendiceal lesions [3]. Michelle Moh et al combined immunohistochemistry to report common SATB (-), SATB2 (+) and CDX-2 (+) in ovarian mucinous tumors, highly indicative of the tumor being derived from the colon or the appendix [2].…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, the increasing level of CA125 while maintaining normal HE4 helps discriminate between benign and malignant ovarian tumors. Our patient showed elevated CA199 and CA125 levels, which can help diagnose appendiceal lesions[ 5 ]. Moh M used immunohistochemistry to identify SATB (-) in ovarian mucinous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study from Wang et al. revealed the mutational landscape of ovary-originating PMP as well as the potential factors that could be used to predict patient survival [ 19 ]. They observed that each PMP patient carried at least one cancer driver gene with mutations, and most patients carried multiple driver genes with mutations.…”
Section: Discussionmentioning
confidence: 99%